RUNX1 cooperates with FLT3-ITD to induce leukemia - Behrens, Kira (J Exp Med, 2017)
Acute myeloid leukemia (AML) is induced by the cooperative action of deregulated genes that perturb self-renewal, proliferation, and differentiation. Internal tandem duplications (ITDs) in the FLT3 receptor tyrosine kinase are common mutations in AML, confer poor prognosis, and stimulate myeloproliferation. AML patient samples with FLT3-ITD express high levels of RUNX1, a transcription factor with known tumor-suppressor function. In this study, to understand this paradox, we investigated the impact of RUNX1 and FLT3-ITD coexpression. FLT3-ITD directly impacts on RUNX1 activity, whereby up-regulated and phosphorylated RUNX1 cooperates with FLT3-ITD to induce AML. Inactivating RUNX1 in tumors releases the differentiation block and down-regulates genes controlling ribosome biogenesis. We identified Hhex as a direct target of RUNX1 and FLT3-ITD stimulation and confirmed high HHEX expression in FLT3-ITD AMLs. HHEX could replace RUNX1 in cooperating with FLT3-ITD to induce AML. These results establish and elucidate the unanticipated oncogenic function of RUNX1 in AML. We predict that blocking RUNX1 activity will greatly enhance current therapeutic approaches using FLT3 inhibitors.